Demethylation of host-cell DNA at the site of avian retrovirus integration - Hejnar, Jirí; Elleder, Daniel; Hájková, Petra; Walter, Jörn; Blazková, Jana; Svoboda, Jan (Biochemical and biophysical research communications, 2003)
The transcriptional activity of an integrated retroviral copy strongly depends on the adjacent host-cell DNA at the site of integration. Transcribed DNA loci as well as cis-acting sequences like enhancers or CpG islands usually permit expression of nearby integrated proviruses. In contrast, proviruses residing close to cellular silencers tend to transcriptional silencing and CpG methylation. Little is known, however, about the influence of provirus integration on the target sequence in the host genome. Here, we report interesting features of a simplified Rous sarcoma virus integrated into a non-transcribed hypermethylated DNA sequence in the Syrian hamster genome. After integration, CpG methylation of this sequence has been lost almost completely and hypomethylated DNA permits proviral transcription and hamster cell transformation by the proviral v-src oncogene. This, however, is not a stable state, and non-transformed revertants bearing transcriptionally silenced proviruses segregate with a high rate. The provirus silencing is followed by DNA methylation of both provirus regulatory regions and adjacent cellular sequences. This CpG methylation is very dense and resistant to the demethylation effects of 5-aza-2(')-deoxycytidine and/or trichostatin A. Our description exemplifies the capacity of retroviruses/retroviral vectors to overcome, at least transiently, negative position effects of DNA methylation at the site of integration.
Keywords: DNA Methylation; geny src; Cell Line; siřičitany; Cell Line, Tumor; metylace DNA; Genes, src; Mesocricetus; Transcription, Genetic; histondeacetylasy; Protein Synthesis Inhibitors; CpG ostrůvky; molekulární sekvence - údaje; křeček rodu Mesocricetus; Agar; Histone Deacetylases; Retroviridae; Azacitidine; Models, Genetic; Enzyme Inhibitors; azacytidin; Hydroxamic Acids; agar; inhibitory syntézy proteinů; genetická transkripce; Cricetinae; Virus Integration; Animals; zvířata; kyseliny hydroxamové; modely genetické; buněčné linie; integrace viru; CpG Islands; Molecular Sequence Data; Sulfites; Terminal Repeat Sequences; nádorové buněčné linie; Decitabine; koncové repetice; inhibitory enzymů; křečci praví; decitabin